Feeding behaviour patterns and water intake in sheep and goats fed alfalfa hay treated with quebracho - Salem A.Z.M.; González J.S.; López S.; Ranilla M.J. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
Eight Merino sheep and eight Alpine goats were used in two experiments. They were fed 20 g dry matter (DM) per kg LW alfalfa hay for 15 days. After this period, four sheep and four goats were given alfalfa hay treated with 50 g quebracho per kg DM (Q) for 60 days, whereas the other animals (control group) were given untreated alfalfa hay (A). Feeds were distributed once daily. Feeding behaviour was recorded on two consecutive days by videotaping the head of the animals. To follow medium-term changes, feeding behaviour was studied in three experimental periods. Time spent eating (ET) and ruminating (RT) were similar with both diets in the three different periods. The number of eating bouts (EB) was not significantly affected by the diet. There was a significant decrease in EB from P1 to P2 and P3 similar in both diets. Water intake was higher when sheep were fed Q diet but was not affected by the diet in goats.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)